Error Analysis in Writing an English Narrative Composition - Paramita Kusumawardhani (Bina Nusantara University, 2015)
The purpose of the research were to know the errors which have been made by the learners in their English narrative composition and it is also to know why they made the errors, to identify the errors made by the learners, to correct the errors, to improve the teaching quality which is appropriate with the curriculum and the syllabus and to get the data and the explanation about the difficulties in studying English especially in writing the English narrative composition. The method used in this research is descriptive method. Descriptive method means the method which tries to give thedata and the explanation about the recent symptoms. The data was taken from 20 students and it was taken by asking the learners to make the English narrative composition, classifying then analyzing the errors found in their composition.The errors that have been found in the compositions are 30 items or 15% for errors of selection, 25 items or 12, 5% for errors of ordering, 115 items or 57, 5% for errors of omission and 30 items or 15% for errors of addition. Some identifying, classifying, analyzing and correcting the errors have been done to correct the errors that have been found. It was done in order to minimize and avoid the same errors happen again in the learners’ English narrative composition.